PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING MENGGUNAKAN MEDIA FLASH PADA MATERI REAKSI REDOKS TERHADAP HASIL BELAJAR SISWA KELAS X SMK NEGERI 2 PONTIANAK - Istiqomah Istiqomah; Elin B Somantri; Tuti Kurniati (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACTThis study aimed by the students’ low learning outcomes class at the elemerith grade X of SMK Negeri 2 Pontianak on chemistry subject, especially in the matter of redox reactions. The aim of this study was to determine differences in learning outcomes class at the elemerith grade X of SMK Negeri 2 Pontianak in the matter redox reactions being taught by cooperative learning model snowball throwing type by flash media with the lecture method by flash media and to determine the influence of cooperative learning model snowball throwing using flash media on learning outcomes class at the elemerith grade X of SMK Negeri 2 Pontianak academic year 2014/2015. This research was Quasi Experimental Research Nonequivalent Control Group Design. The sampling system was simple random sampling technique. This study employed the students of grade X TITL as the samples of experiment group, and the students of grade X TSM as the samples of control group. The techniques of data collections used measurement and observation. Meanwhile the instruments employed that is the achievement test in the form of essay. The calculation results of the post test effect size of 0.83, which meant cooperative learning model snowball throwing type by flash media influence which was 29.67 % and considered high which indicated the positive effect. The results showed differences between the learning outcomes which were taught by using cooperative learning model snowball throwing type by flash media with the lecture method by flash media.Keywords: Learning Outcomes, Snowball Throwing, Redox Reactions, Flash Media